Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1111/j.1523-1755.2004.00929.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of inducible myocardial ischemia in predicting cardiovascular events after renal transplantation

Abstract: IMI was present in 10% of RTR aged > or =50 years, and was predicted by acute rejection and left ventricular hypertrophy. IMI had a strong effect on major cardiovascular events in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Inducible myocardial ischemia was seen in 10% of the patients and was associated with increased future events. 10 These series are limited to patients with advanced renal impairment and are limited by small numbers and small number of events. Our study is also in agreement with a recently published analysis that evaluated the prognostic value of dobutamine stress echo among the entire strata of renal function in 2292 patients.…”
Section: Al-mallah Et Al Myocardial Perfusion Imaging and Renal Functionmentioning
confidence: 99%
“…Inducible myocardial ischemia was seen in 10% of the patients and was associated with increased future events. 10 These series are limited to patients with advanced renal impairment and are limited by small numbers and small number of events. Our study is also in agreement with a recently published analysis that evaluated the prognostic value of dobutamine stress echo among the entire strata of renal function in 2292 patients.…”
Section: Al-mallah Et Al Myocardial Perfusion Imaging and Renal Functionmentioning
confidence: 99%
“…Previous studies showed that DSE might be useful in predicting prognosis in patients with CKD and renal transplantation recipients [36][37][38][39][40]. The largest study evaluating the prognostic value of DSE was among 485 patients with CKD in a study of Bergeron et al According to the data of this study, both ECG and echocardiographic evidence of stress-induced ischemia and the percentage of ischemic segments during DSE were strong independent predictors of mortality, even in patients who subsequently underwent renal transplantation [41].…”
Section: Stress Testsmentioning
confidence: 67%
“…59 More importantly, perfusion abnormalities by RMPI have been consistently found to predict adverse cardiac events in these asymptomatic CKD patients. [56][57][58][59][60] In summary, asymptomatic subjects with CKD have an intermediate likelihood of having occult CAD, and RMPI has been shown to have excellent diagnostic accuracy and independent prognostic value in these patients. However, the comparative effectiveness and cost-effectiveness of RMPI in asymptomatic subjects with CKD is unknown.…”
Section: Chronic Kidney Diseasementioning
confidence: 99%